Does accreditation affect the job satisfaction of general practitioners? A combined panel data survey and cluster randomised field experiment. Issue 8 (August 2020) - Pedersen, Line Bjørnskov; Allen, Thomas; Waldorff, Frans Boch; Andersen, Merethe Kirstine Kousgaard
Highlights: We exploit a randomised stepwise introduction of accreditation in general practice. We survey GP job satisfaction three times during the process from 2016 to 2018. We find no evidence of accreditation affecting GP job satisfaction. This is despite many GPs having negative attitudes towards accreditation. Job satisfaction is related to the perception of the non-monetary incentive scheme. Abstract: A critical question for policy makers in health care is whether external interventions have unintended consequences such as lowering professionals' job satisfaction. We investigate whether a non-monetary incentive, in the form of mandatory accreditation, affects the job satisfaction of Danish GPs. Accreditation of general practice in Denmark was introduced as a cluster randomised stepwise implementation from 2016 to 2018. We measure job satisfaction at three time points: before the randomisation took place, one year into the accreditation process and two years into the accreditation process. We use a balanced panel of GPs who have completed all three waves of the survey (n = 846) and estimate a series of random and mixed effects ordered logit models. Despite many GPs having negative attitudes towards accreditation, we find no evidence of accreditation affecting GP job satisfaction. However, there are negative associations between job satisfaction and perceiving accreditation as a tool for external control. Policy makers are therefore encouraged to carefully inform about new interventions and identify barriers to diminish pre-existing negative perceptions about the incentive.